Warnings from the wild Michael Gunton. - Bristow, Jeremy; Gunton, Michael (BBC Worldwide Ltd., 2009)
All over the planet, temperature increases are affecting wildlife. Some species are spreading to new areas. For others, climate change means extinction. This film draws together the most recent scientific evidence of the effects of the biggest climatic upheaval for 10,000 years.